Histopathology of removed indwelling pleural catheters from patients with malignant pleural diseases. Issue 5 (19th March 2016) - Tobin, Claire L.; Thomas, Rajesh; Chai, Siaw Ming; Segal, Amanda; Lee, Y. C. Gary
Abstract: Background and objective: Indwelling pleural catheters (IPC), used for management of malignant pleural effusions, are often left in situ for a long duration. This study reports for the first time the histological findings of IPCs removed from patients with underlying pleural malignancy. Methods: Forty‐one IPCs ( in situ for median 126 days, interquartile range 43–226) that were removed over a 54‐month period from a single centre were examined. Results: Mesothelioma ( n  = 18) was the predominant underlying malignancy followed by breast, tubo‐ovarian and lung carcinomas. The catheter tubing was fully intact macroscopically in all IPCs. There was no evidence of direct tumour invasion or cancer cell growth on the catheter surfaces in none of the 29 IPCs that were histologically examined. Malignant cells were seen within organizing fibrinous tissues in the lumen of 11 IPCs (27%). A foreign body giant cell reaction was present at the cuff site in all the 29 IPC in which the subcutaneous cuff was examined. Acute ( n  = 10) and/or chronic inflammatory changes were seen in the luminal contents in all 41 IPCs. Conclusion: Our study provides reassuring evidence that the IPC material does not support direct tumour growth or invasion even in the setting of high mesothelioma prevalence. See Editorial, page 787 Abstract : We report for the first time the histological findings of indwelling pleural catheters removed from patients with underlying pleural malignancies. Analyses showed cancer cells in the luminal contents in some cases but no evidence of direct tumour invasion or growth on the catheter surfaces, even in a high mesothelioma prevalence setting. See Editorial, page 787